PROBLEMATIKA PEMBELAJARAN BAHASA ARAB BERBASIS BOARDING SCHOOL - Purwanti, Yanik; Ammar, Farikh Marzuki (Jurnal Dedikasi Pendidikan, 2025)
Boarding school systems have great potential in creating a conducive environment that supports Arabic language proficiency. However, reality shows that the learning process often faces various obstacles, both from the students, educators, curriculum, and boarding school culture. This study was conducted with the aim of identifying and analyzing the challenges of Arabic language learning in educational institutions. The research employed a qualitative design, which involves detailing or elaborating on data obtained directly through interviews, observations, and documentation. The research instrument utilized interview guidelines, and the results were processed using the Atlas. The data was then analyzed and the results presented narratively. The findings of this study indicate that the challenges in Arabic language learning include differences in students' Arabic reading and writing abilities within the same class, the length of exposure to Arabic in previous schools, and low student interest. Therefore, the solutions implemented include grouping students according to their abilities, using engaging teaching methods, and regularly organizing Arabic camps